Environmental standards and their impact on the competitiveness of enterprises - Abdelmoutaleb Bissar (Journal of Excellence for Economics and Management Research, 2020)
This study examines the relationship between environmental standards and competitiveness by assessing the extent and degree of the impact of compliance with environmental standards on competitiveness - this relationship can be evaluated through the application of the Larsen model - and also addresses cases where compliance with environmental standards leads to a slight increase in costs In which improving environmental performance provides opportunities to increase competitiveness and enter new markets. The importance of the study is highlighted as it seeks to focus on the importance of assessing the extent and degree of the impact of specific environmental conditions on the main economic sectors so that it effectively guides the decision-making process and discusses public policy on sustainable development.